The Strategy of Education and Training During The Covid-19 Pandemic - Bayu Adi Laksono (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The purpose of this research is to find out how to manage education and trainingstrategies that not only maintain the existence of the institution but also provide benefits for the perpetrators even though it is carried out during the pandemic. This research was conducted in 6 courses and training institutions in East Java and West Java, from March to April 2021. Using a qualitative approach, starting with the distribution of a preliminary questionnaire, then elaborated by in-depth interviews. The results of the study show that the pandemic provides fundamental changes to the governance or management of educational and training institutions starting from planning, implementation and evaluation. At the planning stage, the course and training institutions change the time, goals, and costs to adapt to pandemic conditions, then create digital marketing strategies, and initial assessments for material efficiency. At the implementation stage, the institution applies virtual learning, as well as face-to-face meeting if it is really necessary to do so. At the evaluation stage, the institution uses a contextual evaluation adapted to the pandemic situation but with the appropriate conditions.